Bridging theory and practice a negotiated ESL curriculum - Acuna-Villacorte, Analiza (2012)
This research attempted to describe the congruency of the general education curriculum in the communication course to AB Broadcasting students of the Bulacan State University (BulSU). The triangulation of perceptions of the students, teachers, and people from the communication industry as respondents has helped in identifying the importance of and the capability of the On-the-Job (OJT) students in the communication skills through a needs analysis survey. The results are compared to the internship performance evaluation ratings given by the cooperating agencies which assessed the outright behaviors of the students as observed in the workplace. Also, the study has been of great help in showing the difference between the perceived importance and capabilities of the students; and it has provided implications for the relevant language needs of the ESL learners. The study was given to a specialized course to gather data to help aid ESL practitioners in developing language curricula in the said state university.
Keywords: Second language acquisition; Evidence-based education